Exploring software engineering knowledge domains (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2024)
Software engineering, as the primary value-based process, is influenced by the culture a given company establishes, formal and informal procedures, and technological improvements introduced during the implementation. Having this in mind it could be articulated further how these innovative methods could result in best practices, communication flows, strong-bonded teams, and successful projects. By adding an organisational domain to the model, the relationships between management's organizational aspects and technological development approaches are discussed.This paper aims to explore and classify the software engineering domains in order to facilitate the process of managing knowledge within ICT companies. Based on a literature overview, a model is proposed which combines the multiple perspectives for adopting knowledge management practices more efficiently.